Evidence from an emerging market economy on the dynamic connection between financial development and economic growth - Yazan Oroud; Hamed Ahmad Almahadin; Mansour Alkhazaleh; Belal Shneikat (Research in Globalization, 2023)
The main goal of this research article is to analyze the dynamic finance-growth connection using Jordan's developing market economy as a case study. For this, indicators of financial development for the relatively long-term period 1980-2020 have been compiled. This relationship is investigated using bounds testing within the autoregressive distributed lag (ARDL) approach. The estimations of both the long-term ARDL model and the short-term ECM model indicate that financial development is crucial to increasing Jordan's economic growth. In addition, the ECT suggests that the convergence of the economic growth process will achieve the long-term equilibrium path through the channels of financial development at a rather rapid rate of adjustment. In contrast, both long-term and short-term empirical results support an inverse link between the real interest rate and economic growth. This study's findings are consistent with the theoretical and empirical arguments of the supply-leading hypothesis, which states that financial development is the driving force behind economic growth. The findings have policy implications, implying that the financial systems of emerging markets are susceptible to interest rate policies. Consequently, the findings have significant ramifications for policymakers who wish to preserve financial development and improve the economic growth of emerging economies.
Keywords: C32; E43; G21; 330; ARDL approach; Bounds testing; Co-integration; Economic growth; Emerging market countries; Financial development